Cenozoic to modern-day source to sink systems of Senegal: A record of provenance, transport, recycling and climate controls. (June 2021) - Mounteney, Ian; Casson, Max; Rushton, Jeremy; Millar, Ian; Dethie, Ndiaye; Redfern, Jonathan
Abstract: This study presents an integrated mineralogical assessment for the provenance of sediments derived from modern-day rivers and Cenozoic deposits in Senegal and Gambia. Two distinct populations are identified from discrimination of the heavy mineral assemblages; the Senegal River sediment, sourced from the West African Craton and Mauritanides and Meso-Cenozoic sediment sourced from the onshore Senegal Basin, demonstrating prevalent recycling of Senegal Basin sediments by the Ferlo, Saloum, Gambia and Casamance Rivers throughout the Quaternary. The Senegal River records the occurrence of amphibole, epidote, garnet and pyroxene, which indicates denudation of Neo to Paleo-Proterozoic granites, low-medium grade meta-sediments and a skarn-type lithology. Meso-Cenozoic recycled sediments within the onshore Senegal Basin exhibit a heavy mineral component which has been modified through the chemical-weathering and diagenesis of less-stable amphibole, pyroxene and garnet. U/Pb dating of zircons from the Casamance and Gambia provinces indicates that, at least in part, the Mesozoic sediments of the onshore Senegal basin may have been ultimately derived from the Leo-Man Shield. Kaolin occurrence is associated with tropical weathering of laterites. The occurrence of terrigenous-smectite sourced from high altitude regions of the Mauritanides and West African Craton is interpreted to have formed under hyper-arid conditions prior to erosion and transportation, during the African humid periods of the Holocene. This integrated mineralogical study of modern-day and Cenozoic sediments has established prevalent recycling of Senegal Basin-sediments by the Ferlo, Saloum, Gambia and Casamance Rivers and continued erosion and recycling of hinterland-sediments via the modern-day Senegal River. This identification of two distinct provenance groups and the strong climatic signal provides the important framework for future studies assessing the source to sink systems during the Meso-Cenozoic. Highlights: An integrated mineralogical provenance study of Cenozoic and modern-day sediments from Senegal. Senegal River erosional catchment includes the Mauritanides, western West African Craton, Kédougou-Kéniéba Inlier. The Ferlo, Saloum, Gambia and Casamance rivers are recycling Meso-Cenozoic sediments from within the onshore Senegal basin. U/Pb dating of detrital zircons suggests Senegalese paleo-river systems may have eroded into the Leo-Man Shield.